Koinfeksi Bronkopneumonia dan Demam Tifoid pada Anak dengan Status Gizi Kurang: Sebuah Laporan Kasus - Fityah Zabrina Hidayat; Shinta Nareswari (CV. Jasa Sukses Abadi, 2026)
Bronchopneumonia and typhoid fever remain major causes of childhood morbidity and mortality in developing countries. Coinfection may aggravate the clinical course, particularly in children with malnutrition. This case report describes the clinical presentation, diagnostic evaluation, and management of bronchopneumonia and typhoid fever coinfection in a malnourished child. A 5-year-8-month-old boy was referred with a 9-day history of fever and persistent cough accompanied by shortness of breath, abdominal pain, and abdominal distension. The patient had a history of controlled epilepsy and was undernourished. Physical examination revealed tachypnea, chest wall retractions, bilateral rhonchi, and abdominal distension. Laboratory investigations showed leukopenia (4,600/µL), thrombocytopenia (101,000/µL), and elevated aspartate aminotransferase (160 U/L). Chest radiography demonstrated bilateral perihilar and paracardial infiltrates consistent with bronchopneumonia, while reactive anti-Salmonella IgM serology (score 6) supported the diagnosis of typhoid fever. The patient received oxygen therapy, intravenous fluid resuscitation with Ringer's lactate, intravenous ceftriaxone and gentamicin, salbutamol nebulization, zinc supplementation, and nutritional support. Progressive clinical improvement was observed, with resolution of fever, decreased respiratory rate, and improvement of respiratory symptoms after seven days of hospitalization. This case highlights the importance of considering coinfection in malnourished children presenting with overlapping respiratory and gastrointestinal manifestations. Early diagnosis, appropriate empirical antibiotic therapy, nutritional rehabilitation, and hygiene education are essential to optimize clinical outcomes and reduce the risk of recurrence.